Neurosurgery training in Nepal: then and now - Chaurasia, Bipin; Raut, Rupesh; Chaurasia, Raushan; Thapa, Amit (Frontiers in Surgery, 2023)
Introduction Neurosurgery training lacks uniformity across the world. Differences in the methods of training adopted during the training period is one of the major problems encountered in the field of neurosurgery all over the world. Moreover, neurosurgery is not “one neurosurgery”; in other words, it is not a unified whole. Material and methods In this study, we attempt to evaluate the present conditions of neurosurgery training in Nepal by exploring different institutions providing the training. Results Due to various factors and challenges, the neurosurgery training provided in Nepal varies in different institutions. Many travel abroad for training due to a lack of sufficient seats in training institutions. Discussion and conclusions Despite the challenges, the future is bright for neurosurgery training in Nepal. With continued investment in education and training, and the adoption of new technologies and techniques, it is likely that the field of neurosurgery will continue to thrive and make a positive impact on the health and well-being of the Nepali population.